Inhibition of pre-emergent herbicide on weedy rice under flooded and saturated soil conditions in rice - Dilipkumar Masilamany,; Erwan Shah Shari,; Nurul Nahar Esa,; Site Noorzuraini Abd Rahman,; Chuah, Tse Seng (Penerbit Universiti Kebangsaan Malaysia, 2024)
Weedy rice poses a formidable challenge in rice cultivation due to its genetic similarity to cultivated rice, making selective herbicides less effective in controlling it without causing harm to the cultivated rice. The potential use of pre-emergent herbicides before rice sowing to inhibit emergence and growth of weedy rice seedlings in the soil remain unknown. Thus, this study aimed to evaluate the responses of weedy rice towards selected pre-emergent herbicides under different soil water conditions and to identify the optimal timing for rice seed sowing following the application of preemergent herbicide to the soil under glasshouse conditions. The results showed that oxadiazon and pretilachlor at 500 g ai ha-1 exhibited higher reductions in weedy rice density and dry weight compared to those given by pendimethalin. Under saturated soil conditions, oxadiazon demonstrated 79 and 80% reductions whereas pretilachlor gave 50 and 59% reductions in weedy rice density and dry weight, respectively. By contrast, under flooded soil conditions both oxadiazon and pretilachlor resulted in complete inhibition of weedy rice. The study showed that delaying rice seed sowing for at least six days after application of pretilachlor or oxadiazon effectively minimized phytotoxic effects on rice. These findings provide valuable insights on the impact of soil water conditions when applying pretilachlor and oxadiazon for effective weedy rice control in direct-seeded rice systems.